The role of populist attitudes in explaining climate change skepticism and support for environmental protection. Issue 6 (18th September 2020) - Huber, Robert A.
ABSTRACT: Conventional wisdom holds that partisanship and political ideology, writ large, are some of the most powerful explanations of attitudes towards climate change and environmental politics. While compelling, most studies focus on a narrow definition of political ideology in the US. This study adds to the literature by assessing the relationship between populism, climate skepticism, and support for environmental protection. Populism offers an orthogonal dimension to partisanship and left-right self-placement, which broadens the scope of the concept. Assessing the UK facilitates understanding the role of political ideology beyond the strong party sorting apparent in the US. Data from the 2015 British Election Study offer strong support for the proposition that populism holds a consequential role in climate and environmental politics.